Diet quality and nutrient distribution while using glucagon-like-peptide-1 receptor agonist: A secondary cross-sectional analysis - Brittany V.B. Johnson; Mary Milstead; Lauren Green; Rachel Kreider; Rachel Jones (Obesity Pillars)
Background: With the rise of glucagon-like-peptide-1 receptor agonist medications (GLP-1RA) for obesity treatment, understanding diet quality can be a valuable tool for providing evidence-based nutrition guidance. However, there is limited data on dietary intake during GLP-1RA treatment. Thus, we analyzed diet quality and nutrient timing while using GLP-1RA. Methods: This was a secondary analysis from a previous cross-sectional online survey questionnaire study involving adults currently using GLP-1RA for weight reduction (N = 69, 49.6 ± 12.3 years old, 35.9 ± 9.1 kg/m2). Three-day food records were analyzed using the Healthy Eating Index (HEI), a validated score that indicates overall diet quality. The 13 HEI components were scored from average 3-day food records and calculated using 95 % confidence intervals (CI). A Bonferroni correction applied significance accepted at p = 0.0038. Additionally, 95 % CI were calculated for calories, macronutrients, and fiber intake reported for breakfast, lunch, dinner, and snacks. Results: A 95 % CI revealed a total HEI score of 54 ± 12 (51.4, 57.3), significantly below the HEI goal (p < 0.0038). All components, except added sugars, were significantly under the max score. There was no significant difference for HEI scores based on duration of GLP-1RA use. The largest number of calories were consumed at dinner, averaging 649 compared to 538, 392, and 391 calories at lunch, breakfast, and snacks, respectively. Further, 40 % of the total daily protein intake occurred at dinnertime. Conclusion: Within the sample of patients using GLP-1RAs, dietary quality was suboptimal for fruits, vegetables, whole grains, seafood and plant proteins, dairy and fatty acids. Future research is needed to determine if HEI scores change before, during, and after GLP-1RA treatments and nutrient timing.